Competitive Gerrymandering and the Popular Vote - Felix J. Bierbrauer; Mattias Polborn (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Gerrymandering undermines representative democracy by creating many uncompetitive legislative districts, and generating the very real possibility that a party that wins a clear majority of the popular vote does not win a majority of districts. We present a new approach to the determination of electoral districts, taking a design perspective. Specifically, we develop a redistricting game between two parties who both seek an advantage in upcoming elections, and show that we can achieve two desirable properties: First, the overall election outcome corresponds to the popular vote. Second, most districts are competitive.
Keywords: D72; C72; 330; Gerrymandering; legislative elections; redistricting